Mental health in pregnant women: Is it being misunderstood? - Guevara-Ríos, Enrique (2024)
Maternal mental health is a fundamental pillar of obstetric care, yet it remains underestimated in clinical settings. Factors such as early adverse experiences, lethal fetal malformations, and pregnancies resulting from sexual violence have a profound psychological impact, increasing the risk of anxiety, depression, and even suicidal ideation. Understanding these realities and strengthening interdisciplinary care are essential to providing comprehensive and compassionate support to pregnant women in vulnerable situations.